Characteristics of CD56-positive cells in guinea pig lung in the dynamics of experimental allergic inflammation - Popko, S. S.; Yevtushenko, V. M.; Zidrashko, H. A. (Zaporozhye Medical Journal, 2022)
The aim of this work is to study morphometric characteristics and distribution of CD56-positive cells in guinea pig lung in the dynamics of experimental allergic inflammation. Materials and methods. We studied the distribution and quantitative changes of CD56-positive cells in guinea pig lung in the dynamics of experimental allergic inflammation using histological, histochemical, immunohistochemical, morphometric and statistical methods. Results. The number of CD56-positive cells increased in the dynamics of experimental ovalbumin-induced allergic inflammation. The increase in the mean number of CD56-positive cells was found in the early period of allergic inflammation (on the 30th day, experimental group II) by 64.5 % (P*/** < 0.001) compared to the control group and by 56.4 % (P* < 0.01) compared to the 23rd day of examinations (experimental group I). The following increase in the mean number of CD56-positive cells by 60.2 % (P*/** < 0.001) was detected in group III compared to the 23rd day of the experiment (group I). However, the mean number of CD56-positive cells was shown to be decreased by 51.5 % (P*/** < 0.001) in group IV compared to the 36th experimental day (group III). Conclusions. CD56-positive cells are located in the pulmonary interstitium. The number of CD56-positive cells is statistically significantly increased in group III in the late stages of the allergic inflammation indicating an active involvement of these cells in maintaining allergen-induced airway inflammation.